PENGARUH EKSPOR, IMPOR KOPI DAN PERTUMBUHAN EKONOMI TERHADAP NERACA PERDAGANGAN INDONESIA TAHUN 2003-2018 - Andriyani, Devi; Rizky, Lian Muhammad (Jurnal Ekonomi Pertanian Unimal, 2023)
This research analyzes the impact of coffee exports, imports, and economic growth on Indonesia's trade balance in 2003-2018. The multiple linear regression analysis method tests the relationship between these variables. Data obtained from Indonesian Plantation Statistics for Coffee Commodities (2019). The research results show that coffee exports significantly negatively impact the trade balance, which means that an increase in coffee exports can cause a decline in the trade balance. On the other hand, coffee imports have a significant negative impact, indicating that increasing coffee imports can contribute to the trade balance deficit. The importance of policies that support increasing the competitiveness of coffee exports, controlling imports, and sustainable economic development to achieve a better trade balance. Further research can explore in-depth micro and macroeconomic aspects to produce more specific policy recommendations.